Analysis of Roles and Responsibilities of Notaries in the Establishment of Cooperatives - Joko Arifin (Sultan Agung Notary Law Review, 2021)
This research method is a qualitative method, with an empirical juridical approach. The specification of this research is descriptive analysis. The data sources used are primary and secondary data obtained through interviews and literature studies, while the data analysis is descriptive analytic. The purpose of this study is to analyze: 1) Implementation of the Deed of Establishment of Cooperatives in Semarang City. 2). The role and responsibilities of a Notary as a Maker of the Deed of Establishment of a Cooperative Business Entity in the City of Semarang. The results of the study concluded: 1) The implementation of the making of the Deed of Establishment of a Cooperative in the City of Semarang, starting from the preparation stage for the formation, the preparation stage for the formation meeting, namely by conducting cooperative counseling, the formation meeting stage attended by a Notary, the application stage to obtain the legalization of the legal entity rights of the Cooperative. Approval is carried out by the Department of Industry, Trade, Cooperatives and MSMEs to examine the articles of association and check the existence of cooperatives. Implementation of the Deed of Establishment of Cooperatives in the City of Semarang, in accordance with Article 1 and Article 15 of Act No. 2 of 2014, as well as in Article 1 paragraph (4) of the Decree of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 98/KEP/M KUKM/IX/2004 concerning Notary as Cooperative Deed Maker. 2) The role and responsibility of the Notary as the Maker of the Deed of Establishment of the Cooperative Business Entity in the City of Semarang is as the maker of the deed of establishment of the Cooperative Business Entity. The notary has the right/legal standing in making the deed of establishment of a cooperative legal entity. Only Notaries who have the right/legal standing in making a deed of establishment of a cooperative legal entity are only certain notaries who have attended briefings in making a deed in connection with a cooperative legal entity and already have a certificate/brevet as a Notary as the Cooperative Deed Making Officer (PPAK).